Development and validation of the well-being in sport questionnaire and sport well-being enhancement profile: two instruments to measure and promote sport-specific well-being - Rose, S.; Burton, D.; Stafford-Son, J.; Grindley, E.; Richardson, C.; Hammermeister, J.; Pickering, M. (Journal of Sport & Exercise Psychology, 2025)
Athletes` overall well-being (WB) often intertwines with their sport WB and vice versa. While holistic WB measures have been explored in nonsport contexts, researchers aim to understand competitive athletes` WB using psychometrically rigorous assessments. Consequently, two interrelated studies were conducted to develop and validate companion instruments: (a) the Well-Being in Sport Questionnaire to gauge outcome-related sport WB and (b) the Sport Well-Being Enhancement Profile to identify strategies for enhancing sport WB. Following contemporary instrument development recommendations, including item development, content, and factor validity, the instruments underwent exploratory factor analysis, exploratory structural covariance modeling, confirmatory factor analysis, and measurement invariance. By utilizing the Well-Being in Sport Questionnaire and Sport Well-Being Enhancement Profile, coaches, athletes, and practitioners can comprehensively understand athletes` WB, facilitating strategies for daily enhancement alongside peak sport performance.